Phylogeography, genetic diversity and population structure of the freshwater stingray, Paratrygon aiereba (Müller & Henle, 1841) (Myliobatiformes: Potamotrygonidae) in the Colombian Amazon and Orinoco basins. (2nd January 2021) - Rizo-Fuentes, Maira A.; Correa-Cárdenas, Camilo A.; Lasso, Carlos A.; Morales-Betancourt, Mónica A.; Barragán-Barrera, Dalia C.; Caballero, Susana
Abstract: The freshwater stingray Paratrygon aiereba have coloration, osteological and morphometric variations that could suggest the existence of more than one species in Colombia. In order to evaluate the phylogeography, population structure and genetic diversity for P. aiereba distributed in the Amazon and Orinoco basins, we amplified Cytochrome oxidase subunit 1 (COI) partial region of mitochondrial DNA ( mtDNA ) in 50 samples from eight different sub-basins. Our results suggest three phylogroups and a vicariance event occurred 43 million years ago proposing how Paratrygon diverged into the basins. A high population structure ( ΦST = 0.692; p  < 0.005) and a value of ( K ) of 3 were defined. A high genetic diversity within phylogroups was found: Phylogroup A ( h  = 0.64; π% = 2.48), Phylogroup B ( h  = 0.552; π% = 1.67), and Phylogroup C ( h  = 0.49; π% = 0.73). These results should be considered in local management plans, conservation programs and reclassification in at least Amazon and Orinoco.